Legal science at the crossroads of the objectivity, requirements and changes - Шишка, Роман Богданович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The author draws attention to the negative phenomena that emerged in the legal science, in particular too large amount of scientists and scientific works and their influence on the legal regulation of social relations. In the article authorial assessments and proposals to increase the level and efficiency of legal science are formulated. Flaws in the legal academic sector and the need for effective decisions to improve it are obvious. This is a non-judgmental setting of the state of science, creation of general and sectoral researches and review of the results, the sample justified and real integration components installation as a prerequisite for creating a common legal space. It appears that such work would be conducted under the auspices of the National Academy of Sciences of Ukraine and its scientific institutions